Erratum to: Elliptic virtual structure constants and generalizations of BCOV-Zinger formula to projective Fano hypersurfaces - Masao Jinzenji; Ken Kuwata (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP12(2024)135